Penguatan usaha kelompok budidaya ikan tawar “Mujur Fish Farm” dimasa pandemi Covid-19 dengan membangun mindset and spirit entrepreneur - Bahri Bahri; Widodo Prastyo; Dicky Dicky Arnendra Dwi Nugraha (Riau Journal of Empowerment, 2021)
The rapid spread of Covid-19 in Indonesia led the government to impose physical distancing and Large-Scale Social Restrictions (PSBB) resulting in declining sales activity. One of the business groups affected by Covid-19 is the Fish Farming Group "Mujur Fish Farm". This devotion aims to foster the mindset and spirit of entrepreneurs, as well as increase knowledge related to the right steps so that products can be sold. The implementation method uses Participatory Rural Appraisal (PRA) by involving the local community. The stage of implementation is through the stage of preparation, planning, implementation and evaluation, and assessment stages. The achievement of this activity is that group members know how to build an entrepreneur mindset in the Covid-19 pandemic by staying positive and creative. The rapid spread of Covid-19 in Indonesia led the government to impose physical distancing and Large-Scale Social Restrictions (PSBB) resulting in declining sales activity. One of the business groups affected by Covid-19 is the Fish Farming Group "Mujur Fish Farm". This devotion aims to foster the mindset and spirit of entrepreneurs, as well as increase knowledge related to the right steps so that products can be sold. The implementation method uses Participatory Rural Appraisal (PRA) by involving the local community. The stage of implementation is through the stage of preparation, planning, implementation and evaluation, and assessment stages. The achievement of this activity is that group members know how to build an entrepreneur mindset in the Covid-19 pandemic by staying positive and creative.